The relationship between renal function and surgical outcomes of patients with proliferative diabetic retinopathy - Liu, Jin; Zhang, Weiwei; Xie, Ping; Yuan, Songtao; Jiang, Lin; Liu, Qinghuai; Hu, Zizhong (Frontiers in Endocrinology, 2022)
Objectives The relationship between renal function and diabetic retinopathy has been controversial. This study is to investigate the influence of renal function on the complex and surgical outcomes of proliferative diabetic retinopathy (PDR). Methods This was a post hoc analysis of the CONCEPT clinical trial. A total of 45 eyes with PDR underwent vitrectomy were included. Based on the estimated glomerular filtration rate (eGFR), they were divided into abnormal renal function group (ARF group) and normal renal function group (NRG group). Baseline PDR complex, intraoperative outcomes (Intraoperative bleeding, frequency of endodiathermy, surgical time, iatrogenic hole, and tamponade) and postoperative outcomes (logMAR best-corrected visual acuity, vitreous re-hemorrhage, and macular edema, follow up at postoperative 1 month and 3 months) were estimated. Vitreous, aqueous humor and serum were collected at the vitrectomy day and Vascular endothelia growth factor-A levels were quantified for all included patients using liquid chip method. Results There was no significant difference in baseline PDR complex, intraoperative and postoperative outcomes between ARF group and NRG group (all P > 0.05). At the vitrectomy day, there was also no difference of Vascular endothelia growth factor-A levels in vitreous, aqueous humor and serum between the two groups (all P > 0.05). Conclusion Our results showed that the renal function seems not parallel to the severity of PDR, neither to the surgical outcomes. This might be interpreted by the similar Vascular endothelia growth factor-A levels in vitreous, aqueous humor and serum between the two groups.